2022
DOI: 10.3390/nu14153119
|View full text |Cite
|
Sign up to set email alerts
|

Nutri-Score: Awareness, Perception and Self-Reported Impact on Food Choices among French Adolescents

Abstract: To date, no studies have evaluated the appropriation of the front-of-pack Nutri-Score labeling among adolescents, although they are both consumers and buyers of food products. Therefore, the objectives of the present study were (1) to assess Nutri-Score awareness, perception and self-reported impact on food choices in French adolescents and (2) to identify the determinants associated with higher Nutri-Score awareness and self-reported impact on food choices. A web-based survey was conducted in November 2021 am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…More recent evidence, highlighted the greater effectiveness of colour-coded labels (such as Nutri-Score and Multiple Traffic Light) over the Reference Intakes, Warning Label and Health Star Rating. The labels continue to perform better in one dimension of decision making-the objective understanding-in 18 countries [141], in Netherlands [142], French adolescents [143], Chile [144] and, other studies, confirm that is associated to a reduction of consumed harmful products [144]. Conversely, other research discussed the effectiveness of bundled FoPL composed by Health Star Rating and Warning Labels [145] in a realworld selection task.…”
Section: What's Next With the Most Recent Contributions?mentioning
confidence: 98%
“…More recent evidence, highlighted the greater effectiveness of colour-coded labels (such as Nutri-Score and Multiple Traffic Light) over the Reference Intakes, Warning Label and Health Star Rating. The labels continue to perform better in one dimension of decision making-the objective understanding-in 18 countries [141], in Netherlands [142], French adolescents [143], Chile [144] and, other studies, confirm that is associated to a reduction of consumed harmful products [144]. Conversely, other research discussed the effectiveness of bundled FoPL composed by Health Star Rating and Warning Labels [145] in a realworld selection task.…”
Section: What's Next With the Most Recent Contributions?mentioning
confidence: 98%
“…Another well‐known color‐coding system is the Nutri‐Score, initially introduced in France in 2017 and later in Belgium, Germany, Luxembourg, the Netherlands, Spain, and Switzerland (IARC & WHO, 2021). Studies conducted in some European countries generally show positive results in terms of the effectiveness of labeling in attracting consumer attention (Dubois et al., 2021), promoting accurate assessment of the nutritional quality of foods (Andreeva et al., 2020; Egnell et al., 2020), and achieving an objective understanding of labeling (Ducrot et al., 2022; Fialon et al., 2020; Packer et al., 2021). However, a study in 12 countries (Argentina, Australia, Bulgaria, Canada, Denmark, France, Germany, Mexico, Singapore, Spain, the UK, and the United States) with 12,015 participants showed that NS, despite being relatively well‐liked (mean score 6.6, which ranged from 6.2 to 6.8) compared to WL, HSR, MTL, and RI, received the lowest mean scores for trust (6.1, while the highest mean score was 6.6 for MTL), comprehensibility (6.7, with the highest being 7.4 for WL), sufficient information (6.3, the highest was 6.9 for MTL), and suitability as a mandatory label (6.8, with MTL and RI tied at the highest average of 7.3) (Talati et al., 2019).…”
Section: Fopl Effects On Consumer Behaviormentioning
confidence: 99%
“…What we do know is that a qualitative study showed that mothers felt that their children, especially younger ones from lower and middle‐income groups, became important multipliers of the messages after the introduction of Chile's WL (Correa et al., 2019). Another recent study has shown that NS tends to influence the purchasing behavior of French youth whose parents use the system for their purchases (Ducrot et al., 2022). Further studies with this population are needed because they appear to be both prescribers and purchasers of food with their parents or caregivers (Correa et al., 2019; Ducrot et al., 2022), and also because many FOPL policies emerge and change, necessitating monitoring.…”
Section: Future Perspectives Of Fopl Implementation In Some Countries...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, consumers, particularly those in vulnerable communities, find the nutrition data panel on the back of packages challenging to read and comprehend, and often overlook. The labeling formats can be broadly classified as nutrient-specific and summary ( Ducrot et al, 2022 ; Hawley et al, 2013 ). The latter provides a general assessment of the product's nutritional quality and is more straightforward for consumers to understand and utilize.…”
Section: Introductionmentioning
confidence: 99%